INNOVATIVE BEHAVIOR ON MILLENNIALS: ANTECEDENT PROACTIVE PERSONALITY AND TASK CONFLICT WITH MODERATING JOB AUTONOMY - Praptini Yulianti; Fardian Putra Arifien (Jurnal Manajemen dan Pemasaran Jasa, 2019)
The objective of this study is to examine the influence of proactive personality on innovative behavior with the mediating of task conflict and also moderating of job autonomy. This research sample is the whole millennial employees on the. PT Pertamina Operational Marketing Regions East Java, amount 172 millennials employee. Data collected with online survey. The result of this is that proactive personality significantly influences innovative behavior and task conflict partially mediates also job autonomy lowered the relationship between proactive personality and task conflict. The study implication isthatjob autonomy has an important role for millennials to reduce task conflict.